2010
DOI: 10.1007/s10620-010-1342-y
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial Factors Are More Important Than Disease Activity in Determining Gastrointestinal Symptoms and Health Status in Adults at a Celiac Disease Referral Center

Abstract: In patients presenting to a CD referral center, psychosocial factors more strongly affect health status and GI symptoms than disease measures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
36
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 48 publications
2
36
0
1
Order By: Relevance
“…Taavela et al [22] reported a significant correlation between the degree of small bowel mucosal damage based on villous height/ crypt depth ratio, anti-tTG serum antibodies, and patient-reported gastrointestinal symptoms. On the contrary, no significant correlation between clinical presentation and mucosal damage in CD was found in a number of other studies [23][24][25], but most of these studies focused on classical versus atypical/silent presentation, while the clinical spectrum of disease may not always fit these definitions.…”
Section: Discussionmentioning
confidence: 88%
“…Taavela et al [22] reported a significant correlation between the degree of small bowel mucosal damage based on villous height/ crypt depth ratio, anti-tTG serum antibodies, and patient-reported gastrointestinal symptoms. On the contrary, no significant correlation between clinical presentation and mucosal damage in CD was found in a number of other studies [23][24][25], but most of these studies focused on classical versus atypical/silent presentation, while the clinical spectrum of disease may not always fit these definitions.…”
Section: Discussionmentioning
confidence: 88%
“…These types of treatment are encouraging results in phase II and III studies and do not depend on patient compliance to the diet (3) . CD, like most chronic diseases, has a negative impact on the quality of life (QOL) of the patient, both for its clinical manifestations that are variable for each individual, and by food restriction that complicates, among other things, interpersonal relationships (8) .…”
mentioning
confidence: 99%
“…Psychiatric distress may also arise along with CD diagnosis. Previous research (5) have shown psychological symptoms and negative impact on the patient's quality of life and adherence of a gluten-free diet. In the United States, a study performed on 101 adult patients concluded that psychosocial factors have a stronger effect on patient's health and gastronomical symptoms incidence than the disease activity as discovered by serologists and historical data.…”
Section: Introductionmentioning
confidence: 98%